Pseudotrachypus ancistrodes, a new combination for Meteoriopsis ancistrodes (Meteoriaceae) - Nath, Virendra; Bansal, Pooja (Phytotaxa, 2013)
The present study attempts to define the current status of Meteoriopsis ancistrodes, which has been identified as a new addition to the South Indian bryoflora. The taxon has been variously treated by different workers from time to time, resulting in its initial placement under Pseudobarbella ancistrodes. Subsequently, in a taxonomic revision of the Meteoriaceae, Pseudobarbella was transferred to and synonymized under Pseudotrachypus. Thus in the present contribution Meteoriopsis ancistrodes is proposed as belonging in Pseudotrachypus, with the new combination P. ancistrodes. Diagnostic characters along with illustrations of the species and distinction from closely related Indian taxa, with which it may be confused, are discussed.